The relationship between plasmapause, solar wind and geomagnetic activity between 2007 and 2011 - G. Verbanac; V. Pierrard; V. Pierrard; M. Bandić; F. Darrouzet; J.-L. Rauch; P. Décréau (Annales Geophysicae, 2015)
Taking advantage of the Cluster satellite mission and especially the observations made by the instrument WHISPER to deduce the electron number density along the orbit of the satellites, we studied the relationships between the plasmapause positions (LPP) and the following LPP indicators: (a) solar wind coupling functions Bz (Z component of the interplanetary magnetic field vector, B, in GSM system), BV (related to the interplanetary electric field; B is the magnitude of the interplanetary magnetic field vector, V is solar wind velocity), and dΦmp/dt (which combines different physical processes responsible for the magnetospheric activity) and (b) geomagnetic indices Dst, Ap and AE. The analysis is performed separately for three magnetic local time (MLT) sectors (Sector1 – night sector (01:00–07:00 MLT); Sector2 – day sector (07:00–16:00 MLT); Sector3 – evening sector (16:00–01:00 MLT)) and for all MLTs taken together. All LPP indicators suggest the faster plasmapause response in the postmidnight sector. Delays in the plasmapause responses (hereafter time lags) are approximately 2–27 h, always increasing from Sector1 to Sector3. The obtained fits clearly resolve the MLT structures. The variability in the plasmapause is the largest for low values of LPP indicators, especially in Sector2. At low activity levels,LPP exhibits the largest values on the dayside (in Sector2) and the smallest on the postmidnight side (Sector1). Displacements towards larger values on the evening side (Sector3) and towards lower values on the dayside (Sector2) are identified for enhanced magnetic activity. Our results contribute to constraining the physical mechanisms involved in the plasmapause formation and to further study the still not well understood related issues.